Attentional focus does not impact locomotor-respiratory coupling in trained runners - Stickford, A. S.; Stickford, J. L.; Fulton, T. J.; Lovci, T. L.; Chapman, R. F. (European Journal of Applied Physiology, 2020)
Purpose: The purpose of this study was to explore relationships between attentional strategies and LRC, running economy, perceived exertion, and dyspnea. Methods: 25 endurance-trained males (VO2max = 68.2 ± 4.7 mL/kg/min) ran for 5 min each at two different submaximal speeds, during which LRC and oxygen consumption (VO2) were measured. The degree of LRC was calculated as the percentage of breaths occurring during the same decile of the step cycle. Attentional focus was assessed at the end of exercise using an Attentional Focusing Questionnaire, with subscales for association, dissociation, and distress. Results: We found no significant relationships between attentional focus measures and LRC. However, dissociation scores were positively correlated with VO2 (r = 0.404), as well as %VO2max (r = 0.474), at the slower running speed. Distress scores were the only attentional focus subscale related to perceived exertion and dyspnea (r = 0.378 to 0.654). Conclusion: These findings suggest attentional focus is not driving the high levels of LRC seen in trained endurance athletes but may relate to running economy and perceptual responses.